2005
DOI: 10.1016/j.jviromet.2005.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A human immunodeficiency virus type 1 protease biosensor assay using bioluminescence resonance energy transfer

Abstract: A sensitive reporter assay to measure human immunodeficiency virus type 1 (HIV-1) protease (PR) activity is described in this manuscript. This assay measures PR activity as a function of the resonance energy transfer (RET) between a donor molecule [humanized sea pansy Renilla reniformis luciferase (hRLuc)] and an energy acceptor molecule, humanized green fluorescent protein (hGFP2) when expressed in mammalian cells. This is a naturally occurring phenomenon and is an emerging and powerful technology that has si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
(67 reference statements)
1
29
0
Order By: Relevance
“…BRET2 Assay-The BRET assay used for determination of the protein/protein interaction has been described previously in detail (15). Briefly, 293T cells were co-transfected with hGFP2-Vif.⌬C and hRLuc-hA3G and harvested 40 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…BRET2 Assay-The BRET assay used for determination of the protein/protein interaction has been described previously in detail (15). Briefly, 293T cells were co-transfected with hGFP2-Vif.⌬C and hRLuc-hA3G and harvested 40 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…The BRET 2 signal is much shorter than that of BRET 1 (Bacart et al, 2008). Previously, the BRET 2 sensor was used to detect thrombin activity in vitro, and HIV protease was expressed with a plasmid vector in the cells (Dacres et al, 2009;Hu et al, 2005). To our knowledge, this is the first report of the use of a BRET 2 -based probe for the detection of a viral protease during natural viral infection and growth.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, by developing BRET-based cellular RTK assays, it has been shown that discriminating pathway specific signals is important to facilitate the pathway specific drug candidate identification process [30], which will eventually require a HTS screen. Also, a HIV protease based BRET2 biosensor assay was developed [51], which can be adapted for high throughput screening of new HIV-1 protease inhibitors. Cells expressing the HIV-1 protease can be employed to screen for antiviral compounds that also target the proteases of other viruses.…”
Section: High-throughput Screeningmentioning
confidence: 99%